The Code of Colorado Springs: Comprising Article XX of the Constitution of the State of Colorado, the Charter, Amendments Thereto, and General Ordinances of the City of Colorado Springs, Colorado 274-75, § 505 (Frank Exline ed., 1914) - (:unkn) unknown (My University, 1914)
No person shall fire or discharge any cannon, gun, pistol or other firearms or set off, fire or explode any torpedo, firecracker, fireball, rocket or other fireworks whatsoever or make or kindle any bonfire,§
Keywords: DISCHARGE